The Relationship Between Cognitive Functions and Indicators of Physical Condition in Men Aged 21-25 Years of Age - Moseychuk, Yuriy; Vaskan, Ivan; Kljus, Olena; Moroz, Olena; Balatska, Larisa; Blagii, Oleksandra; Yarmak, Olena (Journal of Physical Education and Sport ® (JPES), 2018)
The article presents the results of the research of the cognitive functions of men. Altogether 32 men of 21-25 years of age were involved in the research. All of them are students of the Master’s Degree course of the National University of Physical Education and Sport of Ukraine. All the men under study have a high level of motor activity with a predominantly cyclic structure of movements. To obtain an objective assessment of the researched topic, we used the following research methods: analysis of scientific and methodological literature, anthropometric methods, physiological methods, psychophysiological methods. Analysis of the average indicators of the morpho-functional state indicates that the men of 21-25 years of age do not have any deviations from the age standards, and the cardiovascular system works optimally. In men, there is a high level of development of the respiratory system. Analysis of the average results of cognitive functions indicates the high level of self-efficacy and psycho-emotional state, and the average level of development of short-term memory. Low average statistical results are observed only in indicators of attention span and number of mistakes. According to the purpose of the research, we established the structure of the relationship between morphofunctional parameters and the cognitive functions of men aged from 21 to 25 years of age. The presence of reliable correlation interrelationships is observed between the vital capacity of the lungs and the indices of the psychoemotional state, the correlation coefficients are in the range of r = 0.715 at p <0.001 to r = 1.000 at p<0.001; with indicators of short-term memory capacity (STMC) r = 0.698 at p <0.001, and the volume of processed information (VPI) r = 0.757 at p <0.001. High reliable direct and inverse relationships are observed between anthropometric data. In particular, body length and body weight with indicators of psycho-emotional state, the correlation coefficients are in the range of r = 0.500 with p <0.01 to r = 0.980 at p <0.001.
The Relationship Between Cognitive Functions and Indicators of Physical Condition in Men Aged 21-25 Years of Age / Y. Moseychuk, I. Vaskan, O. Kljus, O. Moroz, L. Balatska, O. Blagii, O. Yarmak // Journal of Physical Education and Sport. ─ 2018. ─ Vol. 18, Supplement issue 5. ─ Р. 2181 – 2185.
Keywords: cognitive functions; physical condition; men